(untitled) (Journal of Tikapur Multiple Campus, 2025)
This paper portrays the impact of financial intermediation especially domestic credit to the private sector and broad money supply on GDP growth in Nepal, using annual time series data spanning from 1974 to 2022. The main objectives of the paper are to examine the magnitude and direction of these financial intermediation variables in influencing economic growth of Nepal. The included time series data were a mix of stationary at level and after first difference. Hence, an Autoregressive Distributed Lag (ARDL) model was employed to provide robust framework for analyzing both long-term relationships and short-term fluctuations while maintaining flexibility in lag selection and handling endogeneity. The findings indicate a nuanced relationship between financial factors and GDP growth of Nepal. Specifically, the coefficient of domestic credit to the private sector is positive but statistically insignificant, this suggests that the flow of domestic credit may be either insufficient or inefficiently allocated to significantly contribute Nepalese economic growth. But, the broad money supply as a percentage of GDP shows a strong positive and statistically significant effect. This indicate that increased money supply supports business activities, improves liquidity, spur investments, and eventually fostering economic growth. Moreover, other control variables also display significant relationships with GDP growth of Nepal. Labor force participation and trade openness demonstrate substantial positive effects, while government expenditure shows a modest positive impact. Furthermore, private consumption expenditure emerged as a critical driver of growth, emphasizing the importance of household expenditure in stimulating demand and economic growth. Therefore, these results underscore the necessity of a stable money supply, increased labor force participation, enhanced private consumption, and greater trade openness for sustained economic growth in Nepal. The findings also shed light to explore potential area for policy improvement to strengthen domestic credit allocation to enhance its contribution to economic growth.